Challenges in implementing inclusive development concept in Sustainable Development Goals 2030 - Nurul Hidayat Ab Rahman,; Saidatul Nadia Abd Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The United Nations (UN) has undertaken several international efforts known as the sustainable development plan to preserve the right of development for future generations. This article presents a summary of the previous Millennium Development Goals 2015 (MDGs) that failed to include all people in the sustainability agenda, especially the vulnerable ones. As this situation has widened the society’s gap, the new Sustainable Development Goals 2030 (SDGs 2030) aims to incorporate the concept of inclusiveness in the current development work. This article aims to highlight the challenges to materialize a successful inclusion in the SDGs 2030. It should be explored in more detail to ensure that it can be adequately addressed for the plan to succeed. This writing is based on a pure legal research framework using qualitative methods. Data were collected through library studies and analyzed critically using content analysis method. This paper identifies that stigma and discrimination, special privileges and lack of data are among the barriers in implementing the concept of inclusivity in the SDGs 2030. Therefore, the paper proposes that laws and policy must be established to support this cause. Besides that, the privileges granted must be balanced with assistance to the vulnerable people in order to achieve equality. As for data collection, countries all around the world must work hand in hand to continue making efforts in gathering comprehensive data of the vulnerable groups.